Children of globalization : diasporic coming-of-age novels in Germany, England, and the United States - Quintana Vallejo, Ricardo (New York, NY : Routledge, 2021)
Children of Globalization is the first book-length exploration of contemporary Diasporic Coming-of-age Novels in the context of globalized and de facto multicultural societies. Diasporic Coming-of-age Novels subvert the horizon of expectations of the originating and archetypal form of the genre, the traditional Bildungsroman, which encompasses the works of Johann Wolfgang von Goethe, Charles Dickens, and Jane Austen, and illustrates middle-class, European, "enlightened," and overwhelmingly male protagonists who become accommodated citizens, workers, and spouses whom the readers should imitate. Conversely, Diasporic Coming-of-age Novels have manifold ways of defining youth and adulthood. The culturally-hybrid protagonists, often experiencing intersectional oppression due to their identities of race, gender, class, or sexuality, must negotiate what it means to become adults in their own families and social contexts, at times being undocumented or otherwise unable to access full citizenship, thus enabling complex and variegated formative processes that beg the questions of nationhood and belonging in increasingly globalized societies worldwide.
4. Diasporic Coming-of-age Novels of the Mexican Diaspora in the United States -- 5. Diasporic Coming-of-age Novels of the Greater Antilles Diasporas in the United States -- Part III -- 6. Diasporic Coming-of-age Novels of Eastern European Diasporas in Contemporary Berlin -- 7. The Future of Diasporic Coming-of-age Novels -- References -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Bildungsromans -- History and criticism; German literature -- Minority authors -- History and criticism; English literature -- Minority authors -- History and criticism; American literature -- Minority authors -- History and criticism; Identity politics in literature; Literature and globalization; SOCIAL SCIENCE / Emigration & Immigration; POLITICAL SCIENCE / Globalization